COMBINED PHARMACOTHERAPY IN PATIENTS WITH ARTERIAL HYPERTENSION ASSOCIATED WITH METABOLIC SYNDROME - Abasova, L.I.; Дашдаміров, Р.Л.; Bahshaliev, A.B. (World of Medicine and Biology, 2010)
The study was undertaken to evaluate the antihypertensive effect and influence on some metabolic data of combined therapy of a fixed combination of the angiotensin-converting enzyme inhibitor lisinopril (10 mg) and the dihydropyridine calcium blocker amlodipine (5 mg) in 57 patients with arterial hypertension stage I–II, associated with metabolic syndrome. After 16 weeks of therapy it was found the `optimal blood pressure (BP) lowering during a day on a long-term basis. Moreover, antihypertensive effect was accompanied with positive influence on some data’s of lipid metabolism, which permits the use this combination in patients with arterial hypertension associated with metabolic syndrome.